Comparison of Stretching Exercise Methods and Gender to Improve Flexibility in Sports Performers at Mooja Fitness Center - Payana, Suarsana Dwi; Juliantine, Tite; Daniel Ray, Hamidie Ronald (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
The purpose of this research is for knowing the effect of the stretching method and gender on flexibility. Experimental research method with 2x2 Factorial Design design, which consists of two groups, because the research uses two independent variables with two moderator variables. Frankel et. Al (2013:277). Based on the results of data processing and analysis described in the previous chapter, it is known that the PNF stretching method is more effective than the passive stretching method in increasing muscle and joint flexibility for men and women with a difference in the average stretch score of 1.52. Then on the results of the analysis of differences in muscle and joint flexibility between men and women, it is known that there is a significant difference in the average score of muscle and joint flexibility between men and women where the average score for men is 1.96. In both men and women, there was a significant increase in muscle and joint flexibility between before and after stretching using either the passive method or the PNF method. So the authors can conclude that the results of the study there are significant differences in the average score of muscle and joint flexibility between the PNF method and the passive method. This shows that the PNF stretching method is more effective than the passive stretching method in increasing muscle and joint flexibility in men and women. Utilization of the stretching method can provide real experience for sports players to increase flexibility by using the stretching method, because flexibility is very influential in increasing effectiveness in exercising.